Ispol'zovanie giperbaricheskoi oksigenatsii v tselyakh vosstanovleniya i povysheniya rabotosposobnosti - Slepenchuk, I. E.; Demurov, E. A. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of the study was to reveal the HBO's influence on the athlete's organism, their working capacity and the course of the restitutional processes. 66 cross-country skiers aged from 18 to 22 years acted as the subjects of the research. The methods of pedagogical experiment, pedagogical inspection, testing, questionairing, medicinal-biological inspution and statistical method of the data's analysis were used in the research. The results had shown that the singl influence of HBOcauses the various reactions in the athlete's organism, which can be classified as three types: - favourable, which is characterized by the increasing of the working capacity through the absolute indicies and system's activity; - unfavourable, expressing itself in the decreasing of the physical working capacity througt the absolute indicies and in the increasing functional systems activities' strain; - indifferent, which is characterised by statistically unreliable differences in the working capacity changes according the data of WC170 and functional systems activities.